Breast Cancer 2012 – New Aspects - Kolberg, H.-C.; Lüftner, D.; Lux, M. P.; Maass, N.; Schütz, F.; Fasching, P. A.; Fehm, T.; Janni, W.; Kümmel, S. (Geburtshilfe und Frauenheilkunde, 2012)
Treatment options as well as the characteristics for therapeutic decisions in patients with primary and advanced breast cancer are increasing in number and variety. New targeted therapies in combination with established chemotherapy schemes are broadening the spectrum, however potentially promising combinations do not always achieve a better result. New data from the field of pharmacogenomics point to prognostic and predictive factors that take not only the properties of the tumour but also inherited genetic properties of the patient into consideration. Current therapeutic decision-making is thus based on a combination of classical clinical and modern molecular biomarkers. Also health-economic aspects are more frequently being taken into consideration so that health-economic considerations may also play a part. This review is based on information from the recent annual congresses. The latest of these are the 34th San Antonio Breast Cancer Symposium 2011 and the ASCO Annual Meeting 2012. Among their highlights are the clinically significant results from the CLEOPATRA, BOLERO-2, EMILIA and SWOG S0226 trials on the therapy for metastatic breast cancer as well as further state-of-the-art data on the adjuvant use of bisphosphonates within the framework of the ABCSG-12, ZO-FAST, NSABP-B34 and GAIN trials.
Keywords: CLEOPATRA; pertuzumab; BOLERO-2; everolimus; EMILIA; TDM-1; ABCSG-12; ZO-FAST; NSABP-B34; GAIN